Solve for f -3f-3=9-5f

Math
-3f-3=9-5f
Move all terms containing f to the left side of the equation.
Tap for more steps…
Add 5f to both sides of the equation.
-3f-3+5f=9
Add -3f and 5f.
2f-3=9
2f-3=9
Move all terms not containing f to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
2f=9+3
Add 9 and 3.
2f=12
2f=12
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2f=12 by 2.
2f2=122
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2f2=122
Divide f by 1.
f=122
f=122
Divide 12 by 2.
f=6
f=6
Solve for f -3f-3=9-5f

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top